Perbandingan Pendidikan: Studi Komparatif antara Landasan Pendidikan Nasional dengan Landasan Pendidikan Islam - Fajar Indarsih (MUNAQASYAH : Jurnal Ilmu Pendidikan dan Pembelajaran, 2020)
Abstract: The purpose of education is the main thing in education, because a clear concept of the formulation of educational goals, will significantly influence the success of the implementation of education. The subject and object of education are humans themselves which contain complexity and multi aspects. Therefore the limits and content of the meaning of education - as seen in the definition of the interpretation of education and Islamic education - made by experts also vary. The difference is not separated from its orientation, basic framework, pressure points, and philosophical history. Islamic education and education both have a noble goal of striving for optimal student formation in accordance with the nature of the event. To obtain noble dignity and dignity, it is necessary to have strong educational foundations that are constantly being developed to be better. The foundation of education and Islamic education is very important to develop a dignified education for individuals, families, communities, nations, and countries. Furthermore, education experts and practitioners in Indonesia have the challenge of continuing to work towards the integration of the two education systems by eliminating the dichotomy of general and religious studies.